The superintending officer’s duties under JKR Sarawak form of contract PWD 75 (Ver. 2006) - Engkamat, Frauline (2009)
The JKR Sarawak Form of Contract PWD 75 (Ver. 2006) was officially launched on 2007 to be used for administering the construction contract. Under PWD 75 (Ver. 2006), the Superintending Officer (S.O) will be appointed and is responsible to act reasonably in supervision of the project. The standard of care demanded of a professional is in accordance with the test that was enunciated in the English case of Bolam v. Friern Hospital Management Centre (1957) 2 All ER 47 i.e. it requires a person doing a skilful act to exercise as an ordinary competent human being of the same calling. Since PWD 75 (Ver. 2006) is a new form, therefore the extent of the reasonable supervision is not clear to the practitioner. Thus, in order to determine the reasonable supervision applicable in for PWD 75 (Ver. 2006), a thorough understanding of the art of the supervision is required. Therefore, the objective of this research is to determine the kind(s) of supervision in a construction contract that is reasonable. This research is confined to the traditional procurement, law cases in supervision of construction project, PWD 75 (Ver. 2006), Conditions of Engagement for Professional Services, By-Laws Provisions and documents/manuals regarding supervision. In order to achieve this objective, the research was conducted by analyzing relevant court cases. From the findings, a list of supervisory duty has been determined in Chapter 4. Apart from that, the S.O must give reasonable supervision to the works, as enable him to give an honest certificate that the work has been properly carried out. He is not required personally to measure or check every detail, but should check substantial and important matters, such as, the bottoming of cement floor, especially if failure to do so will result in the work being covered up and therefore not being capable of inspection at a later stage. The adequate supervision is not tested by counting the number of hours spent on the site. The S.O is generally under no duty to instruct the contractor in the manner of performance of his work. In the task of supervision, the S.O, though he may be assisted by the S.O’s Representatives or Assistants to the S.O or both, cannot escape responsibility except perhaps in the smallest matters of detail, by delegation. He may make use of assistants, provided he retains control of the work and does not cease to exercise his own supervision and judgement. As a conclusion, the standard required in the supervision is not great but the risk of being sued remains high and mitigated by several factors.